Information instantly - Bucholtz, Chris (Telephony, 1998)
TimesTen's TimesTen 2.0 Main Memory Manager uses a memory-resident architecture to improve the performance of relational databases. It employs a standard relational database model and standard structured query language. To boost performance, the Main Memory Manager uses algorithms that take advantage of the memory residence of the data store, the information that resides in a large computer system's main memory.